1987
DOI: 10.1007/bf01849396
|View full text |Cite
|
Sign up to set email alerts
|

The future of intrauterine contraception

Abstract: In this review paper some guidelines for IUD use are presented that if followed should reduce the incidence of IUD-related complications. Recent IUD developments are discussed including the levonorgestrel-releasing T, a new variation of the Multiload, and IUDs designed for postpartum insertion. Since significant improvements in IUD safety will most likely result from a better understanding of IUD-related side-effects and adverse reactions, the paper includes recommendations for future IUD research that could e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Only a few studies have reported on the return to fertility for past users of the Multiload. Among 360 women who had their Multiloads removed to become pregnant 69.4% of the nulliparas and 83.6% of the multiparas achieved pregnancy [2]. This study also reported on 15 women who had their Multiloads removed because of PID.…”
Section: Return To Fertility After Iud Removalmentioning
confidence: 64%
See 1 more Smart Citation
“…Only a few studies have reported on the return to fertility for past users of the Multiload. Among 360 women who had their Multiloads removed to become pregnant 69.4% of the nulliparas and 83.6% of the multiparas achieved pregnancy [2]. This study also reported on 15 women who had their Multiloads removed because of PID.…”
Section: Return To Fertility After Iud Removalmentioning
confidence: 64%
“…The most recent addition to the family of Multiload IUDs is the Multiload Mark II [2]. This version of the Multiload was designed to simplify the insertion procedure, reduce the risk of uterine perforation at the time of insertion, and provide greater assurance the IUD is correctly positioned in the uterus after insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of this modified device are in progress, and it remains to be seen whether this alteration in design will make insertions easier, especially in nulliparous women, while still maintaining the impressively low pertinent event rates of its predecessor, the MLCu375 IUD [14].…”
Section: The Multiload Mark IImentioning
confidence: 98%
“…The inserter has also been designed to function as a uterine sound and has a one-handed expulsion action. The insertion mechanism is such that the device cannot be pushed beyond the end of the inserter tube, thus limiting the risk of uterine perforation [14].…”
Section: The Fincoid-350mentioning
confidence: 99%